1972
DOI: 10.1002/ctpp.19720120102
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zur Frage des Plasmapotentials in der positiven Säule von Niederdruckentladungen

Abstract: ZusammenfassungDurch Integration der experimentell aus der DanYvEsTEm-Ana~yse gewonnenen Energieverteilungsfunktionen der Elektronen werden die Elektronenkonzentrationen im Plasma der positiven Saule yon Ne-und He-Niederdruckentladungen bestimmt und mit den aus der Strombilanzgleichung erhaltenen Werten verglichen. Da in die Komentrationsbestimmung aus der bei der DanYvEsmYN-Analyse ermittelten zweiten Ableitung des Sondenstromes die Lage des Plasmapotentials maDgeblich eingeht, kann man indirekt auf daa Raump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The Druyvesteyn [75,89,90] extension of the Langmuir and Mott-Smith probe theory [91][92][93][94][95] allows determination of the electron energy spectrum, regardless of its shape. Druyvesteyn showed that the EEDF can be obtained from expression:…”
Section: Langmuir Probementioning
confidence: 99%
“…The Druyvesteyn [75,89,90] extension of the Langmuir and Mott-Smith probe theory [91][92][93][94][95] allows determination of the electron energy spectrum, regardless of its shape. Druyvesteyn showed that the EEDF can be obtained from expression:…”
Section: Langmuir Probementioning
confidence: 99%